Analyzing the Effects of Artificial Intelligence-Supported Robotic Services in Istanbul Restaurants: A Study on Enhancing Customer Satisfaction and Employee Experience - Qasım, Hebah Ahmad Ali Farid (İstanbul Sabahattin Zaim Üniversitesi, 2024)
With the growing influence of robots in shaping consumer service interactions, businesses are compelled to adjust to this evolving AIcentric commercial landscape. Despite numerous hospitality brands integrating automated robot systems, there is scarce research available on the effects they have on customer contentment and employee engagement. This research investigates the correlation between perceived usability, utility, and enjoyment on satisfaction and continuity of experience during interactions with service robots in Istanbul eateries, along with the impact of different consumer and employee traits on satisfaction levels. A study was conducted involving 156 diners and 15 restaurant staff members, where a combination of quantitative and qualitative approaches was used. The qualitative segment involved interviews with employees regarding their thoughts on collaborating with robots, while the quantitative part focused on gauging customer opinions. Findings suggest that the reception of restaurants with robot assistance by patrons depends on factors such as perceived utility and userfriendliness, with age playing a significant role in satisfaction levels. Primary services were preferred across various service tiers, and overall satisfaction was linked to the likelihood of recommending the experience. Suggestions involve fostering cooperation between policymakers, tech experts, and business leaders to boost the effectiveness of current technologies and encourage inclusivity for the elderly. Resolving satisfaction gaps among customers and staff can maximize the utilization of robots in dining establishments. The findings of this research are beneficial for professionals, scholars, and decisionmakers aiming to explore and capitalize on the capabilities of robots in the hospitality sector.

Tüketici hizmetleri etkileşimlerini şekillendirmede robotların etkisinin artmasıyla birlikte işletmeler, gelişen yapay zeka merkezli ticari ortama uyum sağlamak zorunda kalıyor. Çok sayıda konaklama markasının otomatik robot sistemlerini entegre etmesine rağmen, bunların müşteri memnuniyeti ve çalışan bağlılığı üzerindeki etkilerine ilişkin çok az araştırma bulunmaktadır. Bu araştırma, İstanbul lokantalarındaki servis robotlarıyla etkileşimler sırasında algılanan kullanılabilirlik, fayda ve keyif ile memnuniyet ve deneyimin sürekliliği arasındaki ilişkiyi ve farklı tüketici ve çalışan özelliklerinin memnuniyet düzeyleri üzerindeki etkisini araştırıyor. Nicel ve nitel yaklaşımların bir kombinasyonunun kullanıldığı, 156 olası restoran müşterisini ve 15 restoran personelini kapsayan bir çalışma gerçekleştirildi. Niteliksel bölüm, çalışanlarla robotlarla iş birliği yapma konusundaki düşüncelerine ilişkin röportajları içeriyordu; niceliksel bölüm ise müşteri görüşlerini ölçmeye odaklandı. Bulgular, robot destekli restoranların müşteriler tarafından karşılanmasının, algılanan fayda ve kullanıcı dostu olma gibi faktörlere bağlı olduğunu ve memnuniyet düzeylerinde yaşın önemli bir rol oynadığını göstermektedir. Birincil hizmetler çeşitli hizmet katmanlarında tercih edildi ve genel memnuniyet, deneyimin tavsiye edilme olasılığıyla ilişkilendirildi. Yeniden ifade edilen Öneriler, mevcut teknolojilerin etkinliğini artırmak ve yaşlılar için kapsayıcılığı teşvik etmek amacıyla politika yapıcılar, teknoloji uzmanları ve iş dünyası liderleri arasındaki iş birliğinin geliştirilmesini içerir. Müşteriler ve personel arasındaki memnuniyet uçurumunun çözülmesi, yemekhanelerde robotların kullanımını en üst düzeye çıkarabilir. Bu araştırmanın bulguları, konaklama sektöründe robotların yeteneklerini keşfetmeyi ve bunlardan yararlanmayı amaçlayan profesyoneller, akademisyenler ve karar vericiler için faydalıdır.
İstanbul'daki Restoranlarda Yapay Zeka Destekli Robotik Hizmetlerin Etkilerinin İncelenmesi: Müşteri Memnuniyeti ve Çalışan Deneyiminin Geliştirilmesi Üzerine Bir Çalışma
Keywords: Service Robots; Hospitality Industry; Customer Satisfaction; Employee Experience; Technology Acceptance; Service Level Theory; Hizmet Robotları; Konaklama Endüstrisi; Müşteri Memnuniyeti; Çalışan Deneyimi; Teknoloji Kabulü; Hizmet Seviyesi Teorisi